Classification of technological equipment for homogenization - Паляничка, Надія Олександрівна; Palianychka, Nadiia; Ковальов, Олександр Олександрович; Kovalov, Oleksandr; Черненко Р. О. (Харків: ДБТУ, 2025)
Homogenization refers to a technological process designed to create a uniform mixture from components that are normally immiscible. This technique finds applications in various industries, including agriculture, chemical manufacturing, food processing, pharmaceuticals, and cosmetics. However, its most widespread use is in the dairy sector, particularly in the production of milk-based products. The equipment used for this purpose is known as a homogenizer [1].
Keywords: homogenization; milk-based products